2016
DOI: 10.1128/jcm.03346-15
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Commutability for Clinical Viral Load Testing Using a Digital PCR-Based Reference Standard

Abstract: c Given recent advances in the development of quantitative standards, particularly WHO international standards, efforts to better understand the commutability of reference materials have been made. Existing approaches in evaluating commutability include prediction intervals and correspondence analysis; however, the results obtained from existing approaches may be ambiguous. We have developed a "deviation-from-ideal" (DFI) approach to evaluate commutability of standards and applied it to the assessment of Epste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…EBV (Fryer et al, 2016b) and CMV (Fryer et al, 2016a) WHO International Standards were developed to meet the needs expressed in this way in the guidelines and the recommendations made by the healthcare professionals (Andrews et al, 2011;Gulley and Tang, 2010;Heemann et al, 2011;Kim et al, 2017;Kotton et al, 2013;Navarro et al, 2017;Torre-Cisneros et al, 2016;Wattles et al, 2017). However, the commutability of the EBV (Abeynayake et al, 2014;Ruf and Wagner, 2013;Tang et al, 2016) and CMV (Fryer et al, 2016c;Hayden et al, 2015Hayden et al, , 2013 WHO IS was examined and questioned. For instance, Preiksaitis et al conducted a study using 10 different qPCR assays calibrated to the IS and they determined the viral loads of serial IS dilutions and a blinded panel of CMV positive and negative clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…EBV (Fryer et al, 2016b) and CMV (Fryer et al, 2016a) WHO International Standards were developed to meet the needs expressed in this way in the guidelines and the recommendations made by the healthcare professionals (Andrews et al, 2011;Gulley and Tang, 2010;Heemann et al, 2011;Kim et al, 2017;Kotton et al, 2013;Navarro et al, 2017;Torre-Cisneros et al, 2016;Wattles et al, 2017). However, the commutability of the EBV (Abeynayake et al, 2014;Ruf and Wagner, 2013;Tang et al, 2016) and CMV (Fryer et al, 2016c;Hayden et al, 2015Hayden et al, , 2013 WHO IS was examined and questioned. For instance, Preiksaitis et al conducted a study using 10 different qPCR assays calibrated to the IS and they determined the viral loads of serial IS dilutions and a blinded panel of CMV positive and negative clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that viral DNA in plasma samples is to a large extent free and not associated with viral particles and is also subjected to various degrees of degradation, influencing the results, depending on the amplicon length determined by the PCR-assay design [35]. Thus, standardization of the entire assay including primer and probe design, use of international standards, and assessment of the commutability of reference material is needed before a direct comparison of interlaboratory results can be made with absolute confidence, even with the use of ddPCR [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dPCR can be used as a reference method to assess the commutability of reference standards for qPCR, i.e. the extent to which reference standards behave like patient samples and are consistent across different assays [52]. Recently, dPCR was used to validated standard reference materials for several viruses, such as CMV [53] or Ebola virus [54].…”
Section: Quantitative Accuracymentioning
confidence: 99%